The concept of Education in the Training of Future Engineers - Feruza Islamovna Mamurova (Research Parks Publishing LLC, 2021)
Competent approach - training of future engineers-builders to effectively use the main and additional professional functions provided in the content of the professional activity, as well as the different types of skills acquired in situations encountered in the personal, professional and social life of the student